ENHANCED NETWORK SECURITY USING ZERO TRUST IN SMART HOME NETWORKS AGAINST MAN-IN-THE-MIDDLE ATTACKS - BEWIT RAJ SINGH; Raka Yusuf (Program Studi Teknik Informatika Universitas Khairun, 2025)
The rapid adoption of Internet of Things (IoT) devices in Smart Home environments has increased network vulnerability to internal threats, such as Man-in-the-Middle (MitM) attacks, which traditional security models often fail to address. This study aims to design, simulate, and comparatively analyze the effectiveness of a Zero Trust architecture against a traditional security model in protecting a smart home network from MitM attacks. A comparative experiment was conducted in a GNS3 simulation environment featuring two topologies: a conventional flat network using HTTP and a Zero Trust network implementing microsegmentation via VLANs, Access Control Lists (ACLs), and encrypted HTTPS communication. MitM attacks, specifically ARP Spoofing and packet sniffing, were launched against both scenarios. The results unequivocally show that the traditional network was highly vulnerable, allowing attackers to successfully intercept user credentials in plaintext. In contrast, the Zero Trust architecture completely thwarted the attack; its layered defenses blocked unauthorized traffic and encrypted sensitive data, preventing any credential theft. This research concludes that the Zero Trust model is a significantly more effective and robust security strategy for IoT-based smart homes, providing superior protection against internal threats with minimal performance trade-offs compared to conventional approaches